Best practices in robotic magnetic navigation-guided catheter ablation of cardiac arrhythmias, a position paper of the Society for Cardiac Robotic Navigation - Noten, Anna M. E.; Szili-Torok, Tamas; Ernst, Sabine; Burkhardt, David; Cavaco, Diogo; Chen, Xu; Cheung, Jim W.; de Chillou, Christian; Crystal, Eugene; Cooper, Daniel H.; Gasparini, Maurizio; Geczy, Tamas; et al. (Frontiers in Cardiovascular Medicine, 2024)
Preamble Robotic magnetic navigation (RMN)-guided catheter ablation (CA) technology has been used for the treatment of cardiac arrhythmias for almost 20 years. Various studies reported that RMN allows for high catheter stability, improved lesion formation and a superior safety profile. So far, no guidelines or recommendations on RMN-guided CA have been published. Purpose The aim of this consensus paper was to summarize knowledge and provide recommendations on management of arrhythmias using RMN-guided CA as treatment of atrial fibrillation (AF) and ventricular arrhythmias (VA). Methodology An expert writing group, performed a detailed review of available literature, and drawing on their own experience, drafted and voted on recommendations and summarized current knowledge and practice in the field. Recommendations on RMN-guided CA are presented in a guideline format with three levels of recommendations to serve as a reference for best practices in RMN procedures. Each recommendation is accompanied by supportive text and references. The various sections cover the practical spectrum from system and patient set-up, EP laboratory staffing, combination of RMN with fluoroscopy and mapping systems, use of automation features and ablation settings and targets, for different cardiac arrhythmias. Conclusion This manuscript, presenting the combined experience of expert robotic users and knowledge from the available literature, offers a unique resource for providers interested in the use of RMN in the treatment of cardiac arrhythmias.